Curatorial considerations in commercial art spaces: developments in art galleries and art fairs from 1960 to today - Amelia Abdullahsani (Nanyang Technological University, 2022)
This thesis investigates the curatorial practices in commercial spaces such as art fairs and commercial art galleries. This investigation traces the practices of curating from institutional curating to curating in commercial spaces from the 1960s through today. This thesis examines how this developmental shift has affected curating practices and expanded the roles of curators, as well as to understand why and how curatorial spaces in art fairs and commercial art galleries have become de rigeur. It also looks at how curatorial practices in commercial spaces have encompassed other responsibilities and tasks – emphasising the changing roles of curators.